LEGAL LIABILITY FOR NOTARIES DUE TO THE ISSUANCE OF AUTHENTIC DEEDS RESULTING IN STATE LOSSES - Wardantik, Yuli Endah; Khoidin; Prawesthi, Wahyu (jfpublisher, 2023)
Notaries perform the operational duties of public officials authorized by the state to create authentic legal documents. One of the notary's functions is to provide fee waivers (honorarium) when the public who needs notary services can show evidence of poverty from authorized officials. This research aims to provide insight into the professional practices of notaries involved in corruption cases that harm the state. When a notary commits an irregularity in a deed that results in a criminal case, they must be criminally responsible for whatever they have committed. This research uses the normative juridical method, i.e. law in book research or literature study with statute, conceptual, historical, and system approach. A notary must be held accountable for a deed if it contains a criminal act. The responsibility is in the form of strict sanctions following the law's implementation with the Criminal Code and the Criminal Procedure Code. Notarial deeds that cause criminal cases have evidentiary power as deeds under the hand or become null and void as stipulated in Article 41 of the Notary Public Office Law.